Tick-Induced Cutaneous and Allergic Manifestations: Differential Diagnosis Between Lyme Borreliosis and Alpha-Gal Syndrome - Fitz, Emilia; Brzeźniak , Mikołaj; Daniek, Justyna; Kręcina, Filip; Kaczmarek, Weronika; Gil, Kacper; Drelich, Krzysztof; Karbowniczek, Aleksander; Mokracka, Julia Maria; Grabarczyk, Alicja (Quality in Sport, 2026)
Background. Ticks serve as common vectors for both the infectious Lyme Borreliosis and the allergic Alpha-Gal Syndrome creating significant diagnostic challenges when patients present with non-specific skin reactions. Distinguishing between these entities is vital to prevent the misdiagnosis and to ensure correct treatment, ranging from antibiotics for LB to strict dietary avoidance for AGS. Aim. The primary objective of this review is to provide a comprehensive comparative analysis of the cutaneous and allergic manifestations induced by tick bites, specifically focusing on the differentiation between Lyme Borreliosis and Alpha-Gal Syndrome. Materials and methods. A comprehensive literature search was performed across multiple scientific databases, including PubMed, Web of Science, Scopus, and Google Scholar, for peer-reviewed articles and clinical studies. The search focused on publications in English and Polish to ensure a broad geographical and clinical perspective on tick-borne pathologies. Results. Lyme Borreliosis primarily presents as erythema migrans, whereas Alpha-Gal Syndrome manifests as a unique, delayed allergic reaction (urticaria or anaphylaxis) occurring 3–6 hours after mammalian meat consumption. A key clinical differentiator is the quality of the tick bite. Conclusions. Tick bites represent a common origin for both infectious Lyme Borreliosis and the unique, IgE-mediated Alpha-Gal Syndrome, necessitating a precise differential diagnosis. Distinguishing between these entities is vital, as the hallmark delayed urticaria of Alpha-Gal Syndrome is frequently misdiagnosed as chronic idiopathic urticaria or misunderstood as a primary symptom of a bacterial infection. Enhanced clinical awareness and the implementation of molecular component diagnostics are essential for ensuring the correct therapeutic path, ranging from targeted antibiotic therapy to strict dietary exclusion.